Liquid fermented cereals with added Pediococcus acidilactici did not reduce post-weaning diarrhea in pigs – an Escherichia coli challenge study - Xu, Jiajia; Noel, Samantha Joan; Lauridsen, Charlotte; Lærke, Helle Nygaard; Canibe, Nuria (Frontiers in Veterinary Science, 2023)
The effect of feeding fermented liquid feed (FLF) with added Pediococcus acidilactici to weaning piglets challenged with enterotoxigenic Escherichia coli (ETEC) F4 on aspects of diarrhea, performance, immune responses, and intestinal epithelial barrier function was investigated. A total of 46 weaners (weaning at 27–30 days of age) were assigned to four treatments: (1) Non-challenged and dry feed (Non-Dry); (2) Challenged and dry feed (Ch-Dry); (3) Non-challenged and FLF (Non-Ferm); (4) Challenged and FLF (Ch-Ferm). All groups received the same feed, either dry (Non-Dry and Ch-Dry), or in liquid form (Non-Ferm and Ch-Ferm) in which the cereals with added P. acidilactici (106 CFU/g cereals) had been fermented for 24 h at 30°C. On day 1 and 2 post weaning, Ch-Dry and Ch-Ferm were orally inoculated with 5 mL × 109 CFU ETEC F4/mL, whereas the Non-Dry and Non-Ferm received the same amount of saline. Fecal samples and blood samples were collected through the study period. The microbial composition, concentration of microbial metabolites and nutrient composition indicated that the quality of the FLF was high. In the first week, ADFI of both non-challenged groups was significantly higher (p < 0.05) than that of the Ch-Ferm group. The two challenged groups had higher fecal levels of FaeG gene (ETEC F4 fimbriae) from day 2 to 6 post weaning (p < 0.01), and higher risk of having ETEC F4 present in feces from day 3 to 5 post weaning (p < 0.05) compared to non-challenged groups, indicating the validity of the ETEC challenge model. Generally, ADG of the two groups fed FLF were numerically higher than those fed dry feed. Neither challenge nor FLF affected diarrhea. No significant differences were measured between Ch-Ferm and Ch-Dry regarding the level of plasma haptoglobin and C-reactive protein, hematological parameters or parameters related to epithelial barrier. The data indicated a low level of infection caused by the ETEC challenge, while recovery from weaning stress could be observed. The study showed that a strategy like this can be a way of providing a high level of probiotics to pigs by allowing their proliferation during fermentation.